Два новых вида жуков-усачей (Coleoptera, Cerambycidae) из Казахстана - Данилевский, М.Л. (Вестник зоологии, 1988)
Dorcadion (s. str.) alakoliense sp. n.- Kazakhstan, Alakol Lake, Koktuma; Phytoecia badenkoi sp. n.- Kazakhstan, Narynkol, 1850 m. Typematerial is deposited in Zoological Museum, Moscow University (holotypes) and in Institute of Evolutionary Ecology and Morphology of Animals, Moscow.